Digital Economy: Essence of the Phenomenon, Problem and Risks of Formation and Development - A. A. Volkova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
Today new digital technologies, innovative business models get into all spheres of economic life of society, having an impact on an essence of economy, forming in it high-quality structural changes. The digital economy as a subsystem of economy traditional, differing in active use of digital technologies and turnover of specific electronic goods is as a result formed. The level of development of digital economy closely correlates with country competitiveness that requires special attention of the state and business to its development. In the article the review of development of digital economy in the world and Russia is executed, risks and threats of development of digital economy are revealed and the directions of their overcoming are offered. It is established that today the electronic economy is already beyond especially economic processes. Digitalization takes root into social processes, successful activity of people depends on it in the increasing degree, besides, and there is a large-scale implementation of digital technologies in work of the government organizations and structures. On level of development of digital economy Russia does not take the leading positions in the world, but surely keeps in group of the countries following leaders from year to year improving the positions. Collaboration of the state and business in further development of digital economy is necessary. In this activity, it is necessary to consider a number of the problems allocated in article, risks and threats to concentrate resources and efforts to their neutralizations.